ОБЕРТАЛЬНИЙ МОМЕНТ БЕЗПАЗОВОГО МОМЕНТНОГО ДВИГУНА З ПОСТІЙНИМИ МАГНІТАМИ ТА МАСИВНИМ МАГНІТОПРОВОДОМ СТАТОРА - Ісаєв, Є.В.; Пєтухов, І.С. (Інститут електродинаміки НАН України, Київ, 2024)
The properties of the solid magnetic core of the stator of a slotless torque motor with permanent magnets are considered. It is noted that the solid stator under the conditions of low rotation speed has some advantages over the traditional laminated magnetic circuit. These advantages consist in the cost reduction of the design, its compactness and the low time of production preparation. The mathematical model's assumptions and the input data's limitations are formulated. A model of a static magnetic field with a moving electrically conductive medium is chosen. The two-dimensional model is implemented in the "Magnetic fields" interface of the "COMSOL Multiphysics" software. The maximum torque values were obtained and the optimal number of pole pairs was found. The method of calculating the torque based on eddy current losses in the magnetic medium is used. The decrease in torque with increasing rotor speed is calculated. The correction coefficients of the maximum moment were obtained to correct the results of two-dimensional modelling using a three-dimensional model. References 5, figures 6, tables 1.